A POLÍTICA DE COTAS SOCIAIS PARA O ACESSO AO ENSINO SUPERIOR: O CASO DAS UNIVERSIDADES FEDERAIS MINEIRAS - Sabrina Olimpio Caldas de Castro (Universidade Federal de Santa Catarina, 2017)
This study aimed to observe the differences in academic performance between students who had and those who did not have access to Federal Universities of the Minas Gerais via social policy quotas. Therefore, it considered all the courses of this university who performed the National Examination Performance of Students in 2013. We conducted a descriptive analysis to characterize the group of students, considering variables as the type of school and family income. Subsequently took place one (i) analysis to assess whether the income in Enade of students who attended high school in public schools differs from those coming from private schools and; (ii) the performance of students entering the university through social shares is less than the performance of other students; graphical representation, descriptive statistics of the data analysis and test of difference between independent averages. It was identified that the number of students from public school and low-income is less than the number of students from private schools in the courses analyzed. Moreover, the results showed that no statistically significant difference between the performance of the categories considered.